Sex differences of negative emotions in adults and infants along the prefrontal-amygdaloid brain pathway - Leiming Wu; Zilong Hong; Shujun Wang; Jia Huang; Jixin Liu (NeuroImage)
The neural basis of sex-related differences in processing negative emotions remains poorly understood. The amygdala-related fiber pathways serve as the neuroanatomical foundation for emotion processing. However, the precise sex-related variations within these pathways remain largely elusive. Using diffusion magnetic resonance imaging data from 418 healthy individuals, we identified sex differences in white-matter microstructures of the striato-amygdaloid-prefrontal tracts, particularly the amygdala (Amy)-medial prefrontal cortex (mPFC) pathway. These differences were associated with various neurobiological factors, including pain-related negative emotions, pain sensitivity, neurotransmitter receptors, and gene expressions in the human brain. Our findings suggested that the Amy-mPFC pathway may serve as a neuroanatomical foundation for sex-specific negative emotion processing, driven by specific genetic and neurotransmitter profiles. Notably, we also found similar sex differences in this pathway in an infant imaging dataset, hinting at its developmental significance as a precursor to sex differences in adulthood. These findings underscore the importance of the striato-amygdaloid-prefrontal tracts in sex-related differences in processing negative emotions. This may enhance our understanding of sex-specific emotion regulation and potentially inform future research on strategies for preventing and diagnosing emotional regulation disorders across sexes.